До ґенези українсько-польського конфлікту у ХХ столітті - Зашкільняк, Л. (Україна-Польща: історична спадщина і суспільна свідомість, 2011)
Проаналізовано формування і розвиток ідейних засад українського та польського національних рухів у ХІХ і на початку ХХ ст. у контексті геополітичних процесів у Східній Європі. Показано, що на їх формування у цей час впливали різні суттєві чинники: міцний стереотип "історичної Польщі" як цивілізаційного досягнення поляків; національні рухи (польський та український), що увійшли в безпосередній міжнаціональний конфлікт у Галичині, де в умовах існування австро-угорських демократичних інститутів склалися сприятливі обставини для модернізації національних рухів на засадах нових ідеологій, зокрема й радикальних. Також показано, що війна, яка приховувалась за окремими актами зіткнень і конфліктів в Галичині початку ХХ ст., невдовзі зробилася явною після закінчення Першої світової війни. In the article the Author has analyzed the forming and development of the Ukrainian and Polish national movement’s ideological foundations through the 19 and the beginning of 20th centuries in the context of the geopolitical processes in the Eastern Europe. It is argued that their forming was influenced by several important factors: the stereotype of "historical Poland" as the civilization achievement of Poles. The national movements in Galicia Where the Ukrainian-Polish relation developed to the conflict (the Ukrainian and Polish national movements in Austria-Hungary monarchy have a condition to develop under the modern ideologies including democratic and radical). The radicalization both movements assist the spreading through the villages of myths and stereotypes forming by national intellectuals of previous periods and this created a dangerous situation, which could conduct to the conflict. Modernized Ukrainian and Polish national programs included many historical survivals putting the brakes the adoption of democracy and the possibility of compromise. The author has revealed the war hidden under the separate conflicts in Galicia soon after became evident at the end of World War I.